Pictoplasma : the character encyclopaedia. - Thaler, Peter, ....-; Denicke, Lars, ....- (Berlin : Pictoplasma, 2006)
From the worlds of drawing, graphic design and painting, Pictoplasma examines the latest tendencies in character design. Having closely coincided with the character design movement since 1999, Pictoplasma presents a new, incomparable collection of what has become the world's most popular visual language. Through playful sampling and visual remixing, these characters evade established pictorial norms, and confront the viewer directly and emotionally, regardless of cultural background. Focusing on the graphical roots of contemporary character culture, this volume examines the essential qualities that empower these reduced character depictions with an universal, anthropomorphic appeal. Over 360 pages feature the fresh and surprising work of over 250 international artists, designers and newcomers, including Ana Bagayan, Friends With You, Fons Schiedon, Akinori Oishi, Koralie, Klaus Haapaniemi, Eun-Ha Paek, Nicholas Deakin, and Gary Taxali, among others.Vast in scope and always at the forefront, The Character Encyclopaedia is a comprehensive guide to the most intriguing figures populating the character universe.
Keywords: Computer graphics; Tekenkunst